ANALYSIS OF PRENATAL CARE REGARDING REFERRALS TO HIGH-RISK AND SPECIALIZED CARE IN THE MUNICIPALITY OF ANÁPOLIS (CIPEEX, 2025)
Objective: The present study aimed to analyze whether referrals to high-risk care were satisfactory in the municipality of Anápolis-GO, as well as referrals to other health professionals, in addition to the development of community actions aimed at pregnant women and their families. Methodology: The research analyzed, through an online questionnaire, the care provided by doctors and nurses in the health network of the four macro-regions of Anápolis-GO. Results: Fifty-four responses from 22 units in the municipality were analyzed. Of these, 74% were nurses and only 26% were doctors. It was observed that the largest regions have theoretical flaws in relation to the criteria for referral to high risk. Furthermore, although almost all referrals are made to other professionals, there is a flaw in care due to a lack of professionals in the network. Furthermore, community actions for pregnant women and their families take place on an ongoing basis. Conclusion: It was found that the professionals who responded to the survey need updates on the criteria for high-risk referrals, and it is necessary to hire health professionals to compose the basic team of the units.
Keywords: Prenatal Care; Family Health Strategy; Pregnant Women